Impact of Aging on Conversational Discourse Cohesion in Tamil-Speaking Neurotypical Adults - Selvaraj, Ruba; Vadakkanthara Hariharan, Savitha; Subbiah, Arunan (Forum for Linguistic Studies, 2025)
Aging affects discourse cohesion, leading to challenges such as repetition, vagueness, and word-finding difficulties. While research has focused on Western populations, there is a lack of studies on Tamil-speaking elderly, emphasizing the need for exploration in this demographic. The study aimed to investigate age-related differences in conversational discourse cohesion among neurotypical Tamil-speaking individuals. This study included 80 Tamil-speaking participants, comprising 40 middle-aged adults (aged 44–59) and 40 older adults (aged 60–80), with an equal number of males and females. Participants engaged in conversational discourse tasks that were video recorded. Discourse cohesion was analysed using the Complementary Procedure for Conversational Discourse Analysis (CPCDA) tool. Results showed that older adults had significant impairments in discourse cohesion (p ≤ 0.05), including pronoun use, vague expressions, repeated information, and word-finding difficulties, compared to middle-aged adults, with no significant differences in other cohesion domains. Results suggests that age plays a more significant role in discourse cohesion impairments in later adulthood. Assessing discourse cohesion in aging individuals is crucial for the early detection of linguistic decline. These findings support the integration of discourse analysis into routine clinical evaluations by speech-language pathologists, enabling timely and targeted interventions that help preserve communicative effectiveness and improve the communication quality of life in aging populations.